Total laparoscopic intestinal vaginoplasty as neovaginal reconstruction in an HIV-positive transgender woman. (July 2016) - van der Sluis, Wouter B; Verweij, Stephan P; Özer, Mujde; Meijerink, Wilhelmus J; Bouman, Mark-Bram
A 46-year-old, HIV-positive transgender woman of South American ethnicity consulted our outpatient clinic to discuss the possibilities of a surgical, secondary neovaginal reconstruction because of complete stenosis of her inverted penile skin-lined neovagina. She was taking abacavir/lamivudine and nevirapine as antiretroviral therapy. We successfully performed a total laparoscopic sigmoid vaginoplasty without any complications. There was no short-term morbidity and no complications were reported after 15 months of follow-up. To our knowledge, this is the first report of laparoscopic sigmoid vaginoplasty as vaginal reconstruction in a HIV-positive transgender woman. Worldwide, transgender women have a high burden of HIV infection. This report shows that intestinal vaginoplasty is a feasible surgical option for HIV-positive transgender women in need of vaginal reconstruction. Because patients are again able to engage in penetrative sexual intercourse, we emphasise the importance of practicing safe sex and early initiation of adequate antiretroviral therapy in this patient population.